Optimization of the treatment of pregnant women at risk for miscarriage with thrombophilia of pregnant women - Sodiqova D.R; Yunusalieva D.A (Genius Journals, 2024)
The primary task of Uzbekistan is to protect the reproductive potential of the nation, social and medical support for women during pregnancy and the birth of a healthy child. One of the urgent problems of practical obstetrics, which significantly affects the indicators of perinatal and infant mortality, is miscarriage
Keywords: Pregnant Women; healthy child